Colorimetric Comparison of Internal Bleaching with and without Removing Mineral Trioxide Aggregate (MTA) on Induced Coronal Tooth Discoloration by MTA - Sedigheh Khedmat; Elham Ahmadi; Naghmeh Meraji; Zahra Farhang Fallah (Hindawi Limited, 2021)
Objective. This study aimed to colorimetric comparison of internal bleaching with and without removing mineral trioxide aggregate (MTA) on induced coronal tooth discoloration by MTA cement. In this experimental study, twenty human teeth were prepared. An OrthoMTA barrier was placed 1 mm below the CEJ. The teeth were restored with composite resin and were placed in the aging accelerator machine. Then, the specimens were divided into two groups (n = 10); in group A, part of the OrthoMTA was removed and the glass ionomer was placed on the OrthoMTA, and in group B, the OrthoMTA remained intact. Internal bleaching was performed 5 times in 6-day intervals using 37% carbamide peroxide gel. Color determination was performed in 5 stages: baseline, after OrthoMTA discoloration, before OrthoMTA removal, after OrthoMTA removal, and after bleaching treatment sessions. In group A, 8 specimens reached to ∆E < 3.3 after 2 times internal bleaching treatment, and in group B, 5 specimens reached to ∆E < 3.3 with almost 3 bleaching sessions p>0.05. Additionally, 5 specimens reached to the initial color (baseline) after bleaching treatment, 4 specimens in group A and 1 specimen in group B. After OrthoMTA removal, 2 specimens in group A reached to ∆E < 3.3. There was no significant difference between groups with or without OrthoMTA removal p=0.06. Although, the specimens with OrthoMTA removal required fewer bleaching treatment sessions, and the mean value of ∆E was lower in this group.